Recent Advancements in the Management of Neuropathic Pain - Hamdan, Anas; Galvez, Rafael (Jordan Journal of Pharmaceutical Sciences, 2023)
Neuropathic pain is defined as ‘pain arising as a direct consequence of a lesion or disease affecting the Somatosensory system, regarding the most important aspects of analgesic treatment in NP its strongly advised to make use of a confirmatory questionnaire for NP Dx, such as DN4 or LANSS, as the Screening Tools. Administer analgesic medications in accordance with the strong evidence presented in NP. Keep in mind the medications that have been given the approval for NP. Tricyclic antidepressants, selective serotonin reuptake inhibitors (SNRIs; duloxetine, venlafaxine), and gabapentinoids; pregabalin and gabapentin; alone or in combination with topical (lidocaine patch, capsaicin patch) are all indicated as first-line analgesics for patients with peripheral NP. If a medication from the first line is unsuccessful, try another medication from the same group or move on to the second line. Tramadol and oxycodone are both considered to be analgesics of the second line. Tapentadol as a replacement drug in cases of persistent pain, it may be necessary to mix medications that work via distinct mechanisms of action. Alternatively, in the event that pharmacology is unsuccessful, analgesic invasive treatments may be combined with drugs.